PEMILIHAN LAPTOP ATAU NOTEBOOK DENGAN METODE FUZZY MAMDANI DAN SKORING - Ahmad Taufik; Tiwuk Widiastuti; Nelci D Rumlaklak (J-Icon : Jurnal Komputer dan Informatika, 2018)
The Fuzzy Mamdani method is also known as MinMax method, which finding the minimum value of each rule and the maximum value of the combined consequences of each rule. While scoring is a process of changing the answer of the instrument into numbers which is the quantitative value of ananswer to the items in the instrument. In this study, the authors apply Fuzzy Mamdani and Scoring can be implemented in the manufacture of laptops or notebooks selection applications based on the level of accuracy. The calculation of the accuracy level is based on 5 fuzzy inputs which have 70% portion and10 input scores which have 30% portion. The output of the system in the form of a list of recommended levels of accuracy of selection of laptops/notebooks based on the highest order to the lowest. Based on the testing process then obtained the results: The system can provide convenience for consumers in obtaining the information needed to select the laptops/notebooks right and in line with expectations. This can be evidenced by the results of a survey involving 100 consumers and generate 90% which statesassisted by the application selection of the laptops/notebooks.